ANALYSIS OF ECONOMIC ASPECT WITH IN SUSTAINABILITY FARMING OF CHRYSANTHEMUM GEMAH RIPAH FARMER GROUP AT SEMARANG REGENCY, INDONESIA - Ajeng Kusuma Setiadi; Wiludjeng Roessali; Agus Setiadi (AGROLAND The Agricultural Sciences Journal (e-Journal), 2019)
This study aimed to analyze the stability of chrysanthemum prices, the contribution of chrysanthemum farming income to the total farmer household income, and the income risk of chrysanthemum farming. The study was conducted on October 2018 at the member of GemahRipah Farmer Group of Bandungan District, Semarang Regency, Central Java. Census was used as the research method. Thirty-one farmers who are members of Gemah Ripah Farmer Group and cultivating chrysanthemum chosen as respondents. Data analysis method uses price stability analysis, income contribution analysis, and income risk analysis. The results showed the value of coefficient variation (CV) of price was 49.55%, and this value indicates the price of chrysanthemum was classified as unstable because the price was called stable if it has a coefficient of variation between 10-30%. The average income from chrysanthemum farming was Rp. 7,851,521.61 / month on a land area of 1,168.55 m2. Chrysanthemum farming income contributes 88% to total farmer household income, which means that income from chrysanthemum farming contributes very high. The coefficient variation of income was 39.43% indicates that income risk of chrysanthemum farmers was high because it has more than 30% of the coefficient variation.